Genotoxic risk of ethyl‐paraben could be related to telomere shortening. Issue 6 (20th December 2016) - Finot, F.; Kaddour, A.; Morat, L.; Mouche, I.; Zaguia, N.; Cuceu, C.; Souverville, D.; Négrault, S.; Cariou, O.; Essahli, A.; Prigent, N.; Saul, J.; et al.
Abstract: The ability of parabens to promote the appearance of multiple cancer hallmarks in breast epithelium cells provides grounds for regulatory review of the implication of the presence of parabens in human breast tissue. It is well documented that telomere dysfunction plays a significant role in the initiation of genomic instability during carcinogenesis in human breast cancer. In the present study, we evaluated the genotoxic effect of ethyl 4‐hydroxybenzoate (ethyl‐paraben), with and without metabolic activation (S9), in studies following OECD guidelines. We observed a significant increase in genotoxic damage using the Mouse Lymphoma Assay and in vitro micronucleus (MN) tests in the L5178Y cell line in the presence of S9 only after a short exposure. A high frequency of MN was observed in the TK6 cells after a short exposure (3 h) in the presence of S9 and a long exposure (26 h) without S9. We found significant increases in the MN frequency and induced chromosomal aberrations in the lymphocytes of only one donor after ethyl‐paraben exposure in the presence of S9 after a short exposure. Cytogenetic characterization of the paraben‐treated cells demonstrated telomere shortening associated with telomere loss and telomere deletions in L5178Y and TK6 cells and lymphocytes of the paraben sensitive‐donor. In a control cohort of 68 human lymphocytes, telomere length and telomere aberrations were age‐dependent and showed high inter‐individual variation. This study is the first to link telomere shortening and the genotoxic effect of ethyl paraben in the presence of S9 and raises the possibility that telomere shortening may be a proxy for underlying inter‐individual sensitivity to ethyl‐paraben. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The impact of parabens in human breast tissue remains unclear. We demonstrated a genotoxic effect of ethyl‐paraben with and without metabolic activation (S9) and a correlation between telomere dysfunction and increased genotoxic response after ethyl‐paraben treatment in studies following OECD guidelines. These data demonstrate genotoxicity and a higher MN frequency of cells with telomere shortening in the presence of ethyl‐paraben and could advance our knowledge on the role of paraben in breast cancer cells characterized by drastic telomere shortening.